(3GdQbGHI hGdeQGLYI GdOGNdjI Ydi GdeSJhi GdLRFi hGdcdjs - (3YHO GdaJGM(B, (3GdUMfs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2004)
(3GdQbGHI hGdeQGLYI GdOGNdjI Ydi GdeSJhi GdLRFj(B: (3GdQbGHI, GdQbGHI ef NdGd GdJNWjW, GdQbGHI ef NdGd GdJUeje, GdQbGHI GdOGNdjI, GdeQGLYI GdOGNdjI, GdQbGHI GdOGNdjI hGdeQGLYI GdOGNdjI ddCUhd GdKGHJI, GdQbGHI GdOGNdjI hGdeQGLYI GdOGNdjI, GdQbGHI Ydi GdYed hGdeUQhaGJ, GdQbGHI Ydi GdMSGHGJ GdTNUjI hGdfbOjI(B. (3GdQbGHI hGdeQGLYI Ydi GdeSJhi Gdcdj (B((3eSJhi hMOGJ GdLgGR GdGOGQj ddOhdI(B)(3, CgejI GdQbGHI chXjaI GOGQjI Ydi GdeSJhi Gdcdj, GdQbGHI ef NdGd GdJNWjW Ydi GdeSJhi Gdcdj, GdQbGHI ef NdGd Jbjje GdCOGA, GdebheGJ GdCSGSjI GdQbGHI hGdeQGLYI GdMchejI, GdQbGHI Ydi GdYedjGJ aj GdhMOGJ GdMchejI hOhQ CLgRI GdQbGHI aj JMajRgG(B.s
Keywords: (3GdQbGHI GdeGdjIs; (3eQGLYI GdMSGHGJs